A Review on Graphene: Synthesis Methods, Sources, and Applications - Kartini, Evvy; Setiadi, Tiffanny Angela; Muhammad Fakhruddin (Journal of Batteries for Renewable Energy and Electric Vehicles, 2023)
The carbon allotrope so-called graphene is gaining popularity in the research and industry sector as it exhibits excellent thermal conductivity, mechanical strength, current density, electron mobility, and surface area. These properties of graphene allow them to be incorporated in many different fields to enhance the features of current materials and to be used for ground-breaking research. This review includes three major categories which discuss several ways to synthesize graphene, its sources, and its application, mainly in the field of battery. As there are many ways to produce graphene, this review would try to evaluate which methods would be best for different applications of graphene to overcome the high production cost of graphene, environmental damages, and low purity of graphene.